Customer Variety-Seeking and Brand Switching Intention: An Exploration of the Mediating Role of Customer Engagement - Lysandra Priscilla; Popy Rufaidah (Universitas Negeri Malang, 2023)
This study focuses on determining the impact of customer variety-seeking on brand switching intention by exploring the mediation role of customer engagement in streaming services in Indonesia. The data were gathered using a purposive sampling technique, and valid responses from 124 respondents were analyzed. The study results showed that customer variety-seeking significantly improves customer engagement. This study also found a non-significant direct effect of customer variety-seeking on brand switching intention and a negative significant effect of customer engagement on brand switching intention. In indirect relationships, customer engagement has a significant negative role in mediating customer variety-seeking and brand switching intentions. Aligned with social exchange theory, brand switching intention was found to be minimal since customer engagement is a significant mediator of customer variety-seeking and this switching. The findings have emphasized fostering customer engagement to increase customer retention.Keywords: Customer variety-seeking, Customer engagement, Brand switching intention, Social exchange theory